Using EPANET for determining the hydraulic capacity of a siphon in an irrigation system - Taseski, Goce; Nikola Krstovski (Macedonian Committee on Large Dams, 2023)
Considering the spatial arrangement of the irrigation systems, siphons are often part of the main supply pipelines, which represent objects that are used most often for the passage of the pipeline under a river, road, railway, waterway, etc., and the same hydraulically function as water pipline pressure systems. The purpose of this paper is to demonstrate the use of the software for hydraulic analysis of pipeline pressure systems (EPANET ) to determine the hydraulic capacity of a siphon from an irrigation system. Namely, this paper analyzes a case study of an existing siphon "Makaria" which is part of the Tikvesh irrigation system, where a major accident occurs on part of the siphon. The application of EPANET in solving the specific challenge is crucial in the quick and accurate selection of the optimal diameter of the pipeline, because the existing siphon has a diameter of 1620 mm and at the time of the accident there is no possibility to install a pipeline with the same diameter because its production requires longer time which in this case is a key factor because the water needs are urgent. Accordingly, by using EPANET, hydraulic calculations were made for several variants with the application of different pipelines, from which the selection of the optimal diameter of the pipeline was made and, accordingly, the selection of the material for the pipeline with the basic criterion of ensuring the maximum possible flow of water throughout the siphon.
Keywords: Siphon, Hydraulic analysis, Maximum flow, EPANET